"Data stickiness" in interagency government data sharing: a case study. Issue 6 (7th June 2021) - Zhou, Lihong; Chen, Longqi; Han, Yingying
Abstract : Purpose: The provision of high-quality e-Government services requires efficient and collaborative sharing of data across varied types of government agencies. However, interagency government data sharing (IDS) is not always spontaneous, active and unconditional. Adopting a stickiness theory, this paper reports on a research study, which explores the causes of data stickiness in IDS. Design/methodology/approach: This study employed an inductive case study approach. Twenty-three officials from the government of City M in Hubei Province, Central China, were approached and interviewed using a semi-structured question script. Findings: The analysis of the interview data pointed to 27 causes of data stickiness in five main themes: data sharing willingness; data sharing ability; data articulatability; data residence; and data absorptive capacity. The analysis revealed that interagency tensions and lack of preparedness of individual agencies are the main causes of data stickiness in IDS. Originality/value: The case setting is based on China's Government, but the findings offer useful insights and indications that can be shared across international borders.